Can plethysmography have a greater place in the diagnosis, treatment and follow-up of chronic venous insufficiency? - Taner, Temmuz; Guven, Hakan (The European Research Journal, 2024)
Objectives: Chronic venous insufficiency (CVI) is one of the most common venous diseases. CVI is an important clinical picture with a high prevalence, low quality of life, and high diagnosis and treatment costs. Therefore, diagnosis, follow-up, and treatment are important for the patient's socioeconomic and life quality. In this study, we aimed to better examine a test used in the diagnosis, treatment, and follow-up of CVI. Methods: In this retrospective study, 683 patients diagnosed with CVI, who had endovenous laser ablation (EVLA) indications were evaluated between June 2013 and November 2018. EVLA procedure performed on all patients. Preoperative, postoperative 1st and 6th month Doppler USG (ultrasonography), plethysmography, and VCSS (Venous Clinical Severity Score) questionnaire was made to all patients. Results: As a result of our study, we found that there was a significant difference between the preoperative plethysmography and VCSS results of the patients and the postoperative 1st and 6th month results. With the significant difference in the VCSS questionnaire, we have shown that plethysmography gives accurate results in the diagnosis and treatment of CVI since it is an individual, quantitative, and easy test. Conclusions: EVLA is an effective and safe method in patients with venous insufficiency. Since Doppler USG is person and device dependent, we think that plethysmography, which can be used in every clinical setting and provides quantitative results independent of the person, can be used more frequently in the diagnosis and treatment of venous insufficiency. In addition, we think that plethysmography can be used as a valuable additional method in the diagnosis and follow-up of such patients, due to the venous hemodynamic data that Doppler USG cannot provide.